A kind of graphene TPV particle and preparation method thereof
By introducing modified antioxidants and TiO2-MOF/GN composite materials into TPV materials, the problem of poor volatile organic compounds and antioxidant effects in TPV materials is solved, and better environmental protection and antioxidant properties are achieved.
Patent Information
- Application Number
- CN202311782456.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-12-22
AI Technical Summary
TPV materials produce volatile organic compounds and have poor antioxidant effects during use, which limits their use in places with high environmental protection requirements.
Graphene TPV particles are used, and its formulation includes modified antioxidant and TiO2-MOF/GN composite material. Through the preparation of modified antioxidant and the preparation of TiO2-MOF/GN composite material, the antioxidant properties of the material are improved and Adsorption and degradation ability of volatile organic matter.
Effectively adsorb and degrade volatile organic compounds, improve antioxidant and environmental protection, and avoid the precipitation and volatility of traditional antioxidants.
Smart Images

Figure GHA0000008374890000131 
Figure GHA0000008374890000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a graphene TPV particle and a preparation method thereof. Background Art
[0002] Thermoplastic Vulcanizate (TPV for short) is a product with the advantages of good elasticity, bright color and excellent aging resistance. However, TPV is prone to produce volatile organic matter during the dynamic vulcanization process, which makes the material have a strong odor, which seriously limits the use of TPV, especially in kindergartens, primary and secondary schools, etc., where environmental protection requirements are particularly high. Among them, rubber particles are the most commonly used in school sports fields. Nowadays, rubber particles on the market are added with vulcanizers and need to be formed by high-temperature vulcanization. Waste gas will be generated during the production process, which pollutes the environment. The product will contain carbon disulfide, which is not environmentally friendly. In addition, antioxidants need to be added to improve antioxidant properties, but traditional small molecule antioxidants are easy to precipitate and volatilize, and the antioxidant effect is limited.
[0003] Therefore, how to improve the formula of TPV and solve the problem of TPV materials producing volatile organic matter and poor antioxidant effect during use is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a graphene TPV particle and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A graphene TPV particle comprises the following raw materials in parts by weight: 4-8 parts of polypropylene resin, 10-15 parts of polyurethane resin, 4-8 parts of styrene resin, 4-8 parts of polyvinyl chloride resin, 1-2 parts of organic silicone additives, 10-15 parts of white oil, 20-30 parts of filler, 1-2 parts of modified antioxidant, 4-8 parts of EPDM resin, TiO 2 - 5-10 parts of MOF / GN composite material, 0.1-0.3 parts of vulcanizing agent, 0.1-0.3 parts of vulcanization accelerator, 5-10 parts of pigment;
[0007] The modified antioxidant is prepared by the following steps:
[0008] Step A1, adding aminomethane tripropionic acid to a mixture of chloroform and acetonitrile, stirring and mixing evenly, adding trimethylsilyl chloride at room temperature, reflux for 2 hours, and then cooling to 0°C, and then adding triethylamine and trityl chloride dissolved in chloroform to the reactor, stirring the obtained mixture for 1 hour, and then adding methanol, concentrating, extracting, and drying to obtain intermediate product 1;
[0009] Furthermore, the dosage ratio of aminomethane tripropionic acid, trimethylsilyl chloride, a mixture of chloroform and acetonitrile, triethylamine, trityl chloride, chloroform and methanol is 0.01 mol: 0.01 mol: 18-20 mL: 0.02-0.03 mol: 0.01-0.025 mol: 10 mL: 2 mL, and the mixture of chloroform and acetonitrile is prepared by mixing chloroform and acetonitrile in a volume ratio of 5:1.
[0010] Step A2, the intermediate product 1, triethylamine and aluminum chloride are uniformly mixed in tetrahydrofuran, and then the acryloyl chloride tetrahydrofuran solution is slowly added, and the mixture is reacted for 4-8 hours under ice-water bath and stirring conditions, and then filtered and distilled to obtain the intermediate product 2;
[0011] In step A2, the acyl chloride group on the acryloyl chloride undergoes a substitution reaction with the carboxyl group in the intermediate product 1, thereby introducing a terminal double bond structure, so that it can participate in the introduction of a hindered phenol structure in the subsequent reaction;
[0012] Furthermore, the dosage ratio of the intermediate product 1, triethylamine, tetrahydrofuran, aluminum chloride, and acryloyl chloride tetrahydrofuran solution is 0.1-0.2 mol:80-100 g:100 mL:0.01-0.05 mol:100 mL, and the dosage ratio of acryloyl chloride and tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 0.35-0.65 mol:100 mL.
[0013] Step A3, adding the intermediate product 2 and triethylamine to tetrahydrofuran, mixing and stirring evenly, passing nitrogen for 30 minutes to remove air, then adding 6-di-tert-butyl-4-mercaptophenol, and stirring in a 40-50° C. oil bath for 12-24 hours. After the reaction is completed, the mixture is added to 100 mL of petroleum ether for precipitation for 2 hours, and then the obtained precipitate is added to 40 mL of acetic acid solution, refluxed at 30° C. for 10 minutes, filtered and vacuum dried at 80° C. for 12 hours to obtain a modified antioxidant;
[0014] In step A3, the terminal double bond in the intermediate product 2 reacts with the mercapto group in 6-di-tert-butyl-4-mercaptophenol, thereby introducing a hindered phenol structure into the matrix, improving the antioxidant performance of the matrix. This is because the phenolic hydroxyl group in the system provides hydrogen protons to capture free radicals to generate stable compounds during the antioxidant process, thereby terminating the reaction, improving the antioxidant performance of the matrix, and increasing the aging resistance of the matrix; in addition, the free amino group in the modified antioxidant can also react with the double bond in the system, thereby grafting the modified antioxidant into the system, avoiding the problems of precipitation and volatilization of traditional small molecule antioxidants during production and use;
[0015] Furthermore, the usage ratio of the intermediate product 2, triethylamine, tetrahydrofuran and 6-di-tert-butyl-4-mercaptophenol is 0.01-0.02 mol: 0.2-0.4 g: 35-70 mL: 0.05-0.1 mol.
[0016] The TiO 2 -MOF / GN composites were prepared by the following steps:
[0017] Step B1, adding 2,5-dihydroxyterephthalic acid and 2-aminopyridine to anhydrous ethanol and stirring and mixing evenly, recorded as ligand solution, then stirring and mixing copper nitrate trihydrate in deionized water, adding the ligand solution and stirring for 30 minutes, then transferring to a hydrothermal kettle and placing it at 110°C for reaction for 48 hours. After the reaction is completed, cooling to room temperature, washing with 10 mL of ethanol, filtering, soaking in 50 mL of methanol for 24 hours, washing with methanol, filtering, and vacuum drying at 120°C for 24 hours to obtain Cu-MOF;
[0018] In step B1, copper ions are used as metal centers, 2,5-dihydroxyterephthalic acid and 2-aminopyridine are used together as organic ligands to synthesize Cu-MOF having amino and hydroxyl structures on the surface, thereby improving the ability of the composite material to degrade volatile organic compounds in the matrix. This is because the hydroxyl groups on the surface of Cu-MOF can participate in the formation of ·OH radicals in subsequent reactions; in addition, the amino groups on its surface can react with the carboxyl groups on the surface of graphene in subsequent reactions;
[0019] Furthermore, the usage ratio of 2,5-dihydroxyterephthalic acid, 2-aminopyridine, anhydrous ethanol, copper nitrate trihydrate and deionized water is 0.03-0.04 mol: 0.01-0.02 mol: 50-100 mL: 0.06-0.08 mol: 50-100 mL.
[0020] Step B2, add Cu-MOF to a beaker containing ethanol and ultrasonicate for 1 hour, then slowly add the butyl titanate solution to the beaker and ultrasonicate for 30 minutes, then stir for 1 hour, finally transfer the mixed solution to a reactor, and react at 150°C for 24 hours. After the reaction is completed, wash and freeze-dry for 24 hours to obtain TiO 2 -MOF;
[0021] In step B2, TiO is in situ generated on the Cu-MOF surface using butyl titanate as a titanium source. 2 , TiO 2 The introduction of TiO improves the performance of the material in degrading volatile organic compounds. This is because when visible light is irradiated onto the substrate, 2 Absorbed photon energy, e - is excited to migrate from the valence band to the conduction band, leaving h +, thus generating electron-hole pairs. These holes have sufficient positive potential to react with water molecules and hydroxide ions adsorbed on the surface of the substrate to generate ·OH free radicals. The ·OH free radicals have strong oxidizing properties and can react with volatile organic matter to oxidize the organic matter into H 2 O; the surface of Cu-MOF contains a large number of hydroxyl groups that can react with h + The reaction further promotes the generation of OH radicals, further increasing the TiO 2 Photoactivity;
[0022] Furthermore, the dosage ratio of Cu-MOF, ethanol and butyl titanate solution is 0.01-0.05 g: 10 mL: 25 mL, and the butyl titanate solution is prepared by mixing butyl titanate, deionized water and anhydrous ethanol in the ratio of 5-9 mL: 10 mL: 6-10 mL.
[0023] Step B3, add graphene powder to a beaker containing deionized water and ultrasonically disperse for 30 minutes, then add sodium hydroxide and ultrasonically disperse for 30 minutes, then add bromoacetic acid and ultrasonically disperse for 10 minutes, and then stir at room temperature for 5-10 hours. After the reaction is completed, add NHS / EDC solution and stir for 2 hours, and finally add TiO 2 -MOF reacts at room temperature for 8-12h to obtain TiO 2 -MOF / GN composites;
[0024] In step B3, the carboxyl groups on the graphene surface are first activated using EDC / NHS solution, and then the TiO 2 -MOF is loaded on the surface of graphene (GN) to synthesize TiO 2 -MOF / GN composite material, which can adsorb and degrade volatile organic compounds in the matrix, is due to the use of graphene surface as a platform to play the role of TiO 2 -The synergistic effect between MOF and graphene improves the performance of TiO 2 -MOF dispersion, preventing its aggregation, and using the large specific surface area of graphene to form more adsorption sites, which is conducive to the aggregation of volatile organic compounds (benzene series: such as toluene) on its surface; π-π conjugation effect can also be formed between graphene and toluene molecules to form a stable structure, making it difficult for toluene molecules to break free from the constraints of the composite material surface, thereby further enhancing the composite material's adsorption capacity for toluene; in addition, TiO 2 The electrons in the conduction band can be quickly transferred to the graphene surface and O 2 The reaction generates O 2 - Free radicals, and O 2 - Free radicals can react with volatile organic matter and oxidize it into CO2 , thereby achieving the degradation of volatile organic compounds;
[0025] Further, graphene powder, deionized water, sodium hydroxide, bromoacetic acid, EDC / NHS solution and TiO 2 -MOF usage ratio is 0.1-0.3g:80-120mL:1-2g:2-6g:2-4mL:0.2-0.4g, and NHS / EDC solution is prepared by stirring and mixing 4mg EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide), 2mg NHS (N-hydroxysuccinimide) and 4mL deionized water.
[0026] A method for preparing graphene TPV particles comprises the following steps:
[0027] Step S1, weighing raw materials by weight, mixing styrene resin and white oil for 10-20 minutes, and letting stand for 12-24 hours to obtain a first mixture;
[0028] Step S2, mixing polypropylene resin, polyurethane resin and polyvinyl chloride resin, heating to 180-220°C, and then adding the first mixture, organic silicone additives, fillers, modified antioxidants, EPDM resin, TiO 2 -MOF / GN composite material, vulcanizing agent, vulcanization accelerator and pigment are mixed, then heated to 70-75°C and stirred for 10-15 minutes to obtain a second mixture;
[0029] Step S3, conveying the second mixture to a twin-screw extruder, heating it to 170-180°C, and melt-mixing it under the action of high shear force of the twin-screw extruder to obtain a polymer melt, and the polymer melt is extruded through a 10m long pipeline, cooled by spraying cooling water, air-dried, crushed and sieved to obtain graphene TPV particles. During extrusion molding, the polymer melt temperature is controlled to be 190-195°C, the extrusion port temperature is 170-175°C, and the extrusion speed is 6-10m / min.
[0030] Beneficial effects of the present invention:
[0031] The graphene TPV particles prepared by the present invention can effectively adsorb and degrade volatile organic compounds, and have good antioxidant properties and environmental protection. The preparation of the modified antioxidant enables it to have a longer-lasting antioxidant property in the matrix, avoiding the problems of precipitation and volatilization caused by it during production and use; TiO 2 -The preparation of MOF / GN composite materials improves the material's ability to adsorb and degrade volatile organic compounds and has certain environmental protection properties.
[0032] The hindered phenol structure is introduced into the matrix in the modified antioxidant, which improves the antioxidant performance of the matrix. This is because the phenolic hydroxyl groups in the system will provide hydrogen protons to capture free radicals to generate stable compounds during the antioxidant process, thereby terminating the reaction, improving the antioxidant performance of the matrix, and increasing the aging resistance of the matrix; in addition, the free amino groups in the modified antioxidant can also react with the double bonds in the system, thereby grafting the modified antioxidant into the system, avoiding the precipitation, volatilization and other problems that occur in traditional small molecule antioxidants during production and use.
[0033] TiO 2 In-situ generation of TiO on the Cu-MOF surface using butyl titanate as a titanium source in MOF / GN composites 2 , TiO 2 The introduction of TiO improves the performance of the material in degrading volatile organic compounds. This is because when visible light is irradiated onto the substrate, 2 Absorbed photon energy, e - is excited to migrate from the valence band to the conduction band, leaving h + , thus generating electron-hole pairs. These holes have sufficient positive potential to react with water molecules and hydroxide ions adsorbed on the surface of the substrate to generate ·OH free radicals. The ·OH free radicals have strong oxidizing properties and can react with volatile organic matter to oxidize the organic matter into H 2 O; the surface of Cu-MOF contains a large number of hydroxyl groups that can react with h + The reaction further promotes the generation of OH radicals, further increasing the TiO 2 In addition, TiO 2 The electrons in the conduction band can be quickly transferred to the graphene surface and O 2 The reaction generates O 2 - Free radicals, and O 2 - Free radicals can react with volatile organic matter and oxidize it into CO 2 , thereby achieving the degradation of volatile organic compounds. Using the graphene surface as a platform, the TiO 2 -The synergistic effect between MOF and graphene improves the performance of TiO 2 -MOF's dispersibility prevents its aggregation, and uses the large specific surface area of graphene to form more adsorption sites, which is conducive to the aggregation of volatile organic compounds (benzene series: such as toluene) on its surface; in addition, a π-π conjugation effect can be formed between graphene and toluene molecules to form a stable structure, making it difficult for toluene molecules to break free from the constraints of the composite material surface, thereby further enhancing the composite material's adsorption capacity for toluene. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] 1) The modified antioxidant is prepared by the following steps:
[0037] Step A1, add aminomethane tripropionic acid to a mixture of chloroform and acetonitrile, stir and mix evenly, add trimethylsilyl chloride at room temperature, reflux for 2 hours, and then cool to 0°C, then add triethylamine and trityl chloride dissolved in chloroform to the reactor, stir the obtained mixture for 1 hour, then add methanol, concentrate, extract and dry to obtain intermediate product 1, the amount ratio of aminomethane tripropionic acid, trimethylsilyl chloride, chloroform and acetonitrile, triethylamine, trityl chloride, chloroform and methanol is 0.01 mol: 0.01 mol: 18 mL: 0.02 mol: 0.01 mol: 10 mL: 2 mL, and the mixture of chloroform and acetonitrile is prepared by mixing chloroform and acetonitrile in a volume ratio of 5: 1;
[0038] Step A2, the intermediate product 1, triethylamine, and aluminum chloride are uniformly mixed in tetrahydrofuran, and then the acryloyl chloride tetrahydrofuran solution is slowly added, and the mixture is reacted for 4 hours under ice-water bath and stirring conditions, filtered and distilled to obtain the intermediate product 2, the amount ratio of the intermediate product 1, triethylamine, tetrahydrofuran, aluminum chloride, and acryloyl chloride tetrahydrofuran solution is 0.1 mol: 80 g: 100 mL: 0.01 mol: 100 mL, and the amount ratio of acryloyl chloride to tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 0.35 mol: 100 mL;
[0039] Step A3, add the intermediate product 2 and triethylamine to tetrahydrofuran, mix and stir evenly, pass nitrogen for 30 minutes to remove air, then add 6-di-tert-butyl-4-mercaptophenol, and stir in a 40°C oil bath for 12 hours. After the reaction is completed, add the mixture to 100mL of petroleum ether and precipitate for 2 hours, then add the resulting precipitate to 40mL of acetic acid solution, reflux at 30°C for 10 minutes, filter and vacuum dry at 80°C for 12 hours to obtain a modified antioxidant. The amount ratio of the intermediate product 2, triethylamine, tetrahydrofuran and 6-di-tert-butyl-4-mercaptophenol is 0.01mol:0.2g:35mL:0.05mol.
[0040] 2) TiO 2 -MOF / GN composites were prepared by the following steps:
[0041] Step B1, adding 2,5-dihydroxyterephthalic acid and 2-aminopyridine to anhydrous ethanol and stirring and mixing evenly, recorded as a ligand solution, and then stirring and mixing copper nitrate trihydrate in deionized water, adding the ligand solution and stirring for 30 minutes, then transferring to a hydrothermal kettle, and placing it at 110°C for reaction for 48 hours. After the reaction is completed, cooling to room temperature, washing with 10mL of ethanol, filtering, soaking in 50mL of methanol for 24 hours, washing with methanol, filtering, and vacuum drying at 120°C for 24 hours to obtain Cu-MOF, the amount ratio of 2,5-dihydroxyterephthalic acid, 2-aminopyridine, anhydrous ethanol, copper nitrate trihydrate and deionized water is 0.03mol:0.01mol:50mL:0.06mol:50mL;
[0042] Step B2, add Cu-MOF to a beaker containing ethanol and ultrasonicate for 1 hour, then slowly add the butyl titanate solution to the beaker and ultrasonicate for 30 minutes, then stir for 1 hour, finally transfer the mixed solution to a reactor, and react at 150°C for 24 hours. After the reaction is completed, wash and freeze-dry for 24 hours to obtain TiO 2 -MOF, Cu-MOF, ethanol and butyl titanate solution were used in a ratio of 0.01 g: 10 mL: 25 mL, and the butyl titanate solution was prepared by mixing butyl titanate, deionized water and anhydrous ethanol in a ratio of 5 mL: 10 mL: 6 mL;
[0043] Step B3, add graphene powder to a beaker containing deionized water and ultrasonically disperse for 30 minutes, then add sodium hydroxide and ultrasonically disperse for 30 minutes, then add bromoacetic acid and ultrasonically disperse for 10 minutes, and then stir at room temperature for 5 hours. After the reaction is completed, add NHS / EDC solution and stir for 2 hours, and finally add TiO 2 -MOF was reacted at room temperature for 8h to obtain TiO 2 -MOF / GN composites, graphene powder, deionized water, sodium hydroxide, bromoacetic acid, EDC / NHS solution and TiO 2 -MOF dosage ratio was 0.1 g:80 mL:1 g:2 g:2 mL:0.2 g, and NHS / EDC solution was prepared by stirring and mixing 4 mg EDC, 2 mg NHS, and 4 mL deionized water.
[0044] Example 2
[0045] 1) The modified antioxidant is prepared by the following steps:
[0046] Step A1, add aminomethane tripropionic acid to a mixture of chloroform and acetonitrile, stir and mix evenly, add trimethylsilyl chloride at room temperature, reflux for 2 hours, and then cool to 0°C, then add triethylamine and trityl chloride dissolved in chloroform to the reactor, stir the obtained mixture for 1 hour, then add methanol, concentrate, extract and dry to obtain intermediate product 1, the amount ratio of aminomethane tripropionic acid, trimethylsilyl chloride, chloroform and acetonitrile, triethylamine, trityl chloride, chloroform and methanol is 0.01 mol: 0.01 mol: 18 mL: 0.025 mol: 0.02 mol: 10 mL: 2 mL, and the mixture of chloroform and acetonitrile is prepared by mixing chloroform and acetonitrile in a volume ratio of 5: 1;
[0047] Step A2, the intermediate product 1, triethylamine, and aluminum chloride are uniformly mixed in tetrahydrofuran, and then the acryloyl chloride tetrahydrofuran solution is slowly added, and the mixture is reacted for 6 hours under ice-water bath and stirring conditions, filtered and distilled to obtain the intermediate product 2, the amount ratio of the intermediate product 1, triethylamine, tetrahydrofuran, aluminum chloride, and acryloyl chloride tetrahydrofuran solution is 0.15 mol: 90 g: 100 mL: 0.03 mol: 100 mL, and the amount ratio of acryloyl chloride to tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 0.5 mol: 100 mL;
[0048] Step A3, add the intermediate product 2 and triethylamine to tetrahydrofuran, mix and stir evenly, pass nitrogen for 30 minutes to remove air, then add 6-di-tert-butyl-4-mercaptophenol, and stir in a 45°C oil bath for 18 hours. After the reaction is completed, add the mixture to 100mL of petroleum ether and precipitate for 2 hours, then add the resulting precipitate to 40mL of acetic acid solution, reflux at 30°C for 10 minutes, filter and vacuum dry at 80°C for 12 hours to obtain a modified antioxidant. The amount ratio of the intermediate product 2, triethylamine, tetrahydrofuran and 6-di-tert-butyl-4-mercaptophenol is 0.015mol:0.3g:50mL:0.075mol.
[0049] 2) TiO 2 -MOF / GN composites were prepared by the following steps:
[0050] Step B1, adding 2,5-dihydroxyterephthalic acid and 2-aminopyridine to anhydrous ethanol and stirring and mixing evenly, recorded as ligand solution, then stirring and mixing copper nitrate trihydrate in deionized water, adding the ligand solution and stirring for 30 minutes, then transferring to a hydrothermal kettle, and placing it at 110°C for reaction for 48 hours. After the reaction is completed, cooling to room temperature, washing with 10mL of ethanol, filtering, soaking in 50mL of methanol for 24 hours, washing with methanol, filtering, and vacuum drying at 120°C for 24 hours to obtain Cu-MOF, the amount ratio of 2,5-dihydroxyterephthalic acid, 2-aminopyridine, anhydrous ethanol, copper nitrate trihydrate and deionized water is 0.035mol:0.015mol:75mL:0.07mol:75mL;
[0051] Step B2, add Cu-MOF to a beaker containing ethanol and ultrasonicate for 1 hour, then slowly add the butyl titanate solution to the beaker and ultrasonicate for 30 minutes, then stir for 1 hour, finally transfer the mixed solution to a reactor, and react at 150°C for 24 hours. After the reaction is completed, wash and freeze-dry for 24 hours to obtain TiO 2 -MOF, Cu-MOF, ethanol and butyl titanate solution were used in a ratio of 0.03 g: 10 mL: 25 mL, and the butyl titanate solution was prepared by mixing butyl titanate, deionized water and anhydrous ethanol in a ratio of 7 mL: 10 mL: 8 mL;
[0052] Step B3, add graphene powder to a beaker containing deionized water and ultrasonically disperse for 30 minutes, then add sodium hydroxide and ultrasonically disperse for 30 minutes, then add bromoacetic acid and ultrasonically disperse for 10 minutes, and then stir at room temperature for 7 hours. After the reaction is completed, add NHS / EDC solution and stir for 2 hours, and finally add TiO 2 -MOF was reacted at room temperature for 10 h to obtain TiO 2 -MOF / GN composites, graphene powder, deionized water, sodium hydroxide, bromoacetic acid, EDC / NHS solution and TiO 2 -MOF was used in a ratio of 0.2 g:100 mL:1.5 g:4 g:3 mL:0.3 g, and the NHS / EDC solution was prepared by stirring and mixing 4 mg EDC, 2 mg NHS, and 4 mL deionized water.
[0053] Example 3
[0054] 1) The modified antioxidant is prepared by the following steps:
[0055] Step A1, adding aminomethane tripropionic acid to a mixture of chloroform and acetonitrile, stirring and mixing evenly, adding trimethylsilyl chloride at room temperature, reflux for 2 hours, and then cooling to 0°C, and then adding triethylamine and trityl chloride dissolved in chloroform to the reactor, stirring the obtained mixture for 1 hour, and then adding methanol, concentrating, extracting, and drying to obtain intermediate product 1, the amount ratio of aminomethane tripropionic acid, trimethylsilyl chloride, chloroform and acetonitrile, triethylamine, trityl chloride, chloroform and methanol is 0.01 mol: 0.01 mol: 20 mL: 0.03 mol: 0.025 mol: 10 mL: 2 mL, and the mixture of chloroform and acetonitrile is prepared by mixing chloroform and acetonitrile in a volume ratio of 5: 1;
[0056] Step A2, the intermediate product 1, triethylamine, and aluminum chloride are uniformly mixed in tetrahydrofuran, and then the acryloyl chloride tetrahydrofuran solution is slowly added, and the mixture is reacted for 8 hours under ice-water bath and stirring conditions, filtered and distilled to obtain the intermediate product 2, wherein the amount ratio of the intermediate product 1, triethylamine, tetrahydrofuran, aluminum chloride, and acryloyl chloride tetrahydrofuran solution is 0.2 mol: 100 g: 100 mL: 0.05 mol: 100 mL, and the amount ratio of acryloyl chloride to tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 0.65 mol: 100 mL;
[0057] Step A3, add the intermediate product 2 and triethylamine to tetrahydrofuran, mix and stir evenly, pass nitrogen for 30 minutes to remove air, then add 6-di-tert-butyl-4-mercaptophenol, and stir in a 50°C oil bath for 24 hours. After the reaction is completed, add the mixture to 100mL of petroleum ether and precipitate for 2 hours, then add the resulting precipitate to 40mL of acetic acid solution, reflux at 30°C for 10 minutes, filter and vacuum dry at 80°C for 12 hours to obtain a modified antioxidant. The amount ratio of the intermediate product 2, triethylamine, tetrahydrofuran and 6-di-tert-butyl-4-mercaptophenol is 0.02mol:0.4g:70mL:0.1mol.
[0058] 2) TiO 2 -MOF / GN composites were prepared by the following steps:
[0059] Step B1, adding 2,5-dihydroxyterephthalic acid and 2-aminopyridine to anhydrous ethanol and stirring and mixing evenly, recorded as ligand solution, then stirring and mixing copper nitrate trihydrate in deionized water, adding the ligand solution and stirring for 30 minutes, then transferring to a hydrothermal kettle, and placing it at 110°C for reaction for 48 hours. After the reaction is completed, cooling to room temperature, washing with 10mL of ethanol, filtering, soaking in 50mL of methanol for 24 hours, washing with methanol, filtering, and vacuum drying at 120°C for 24 hours to obtain Cu-MOF, the amount ratio of 2,5-dihydroxyterephthalic acid, 2-aminopyridine, anhydrous ethanol, copper nitrate trihydrate and deionized water is 0.04mol:0.02mol:100mL:0.08mol:100mL;
[0060] Step B2, add Cu-MOF to a beaker containing ethanol and ultrasonicate for 1 hour, then slowly add the butyl titanate solution to the beaker and ultrasonicate for 30 minutes, then stir for 1 hour, finally transfer the mixed solution to a reactor, and react at 150°C for 24 hours. After the reaction is completed, wash and freeze-dry for 24 hours to obtain TiO 2 -MOF, Cu-MOF, ethanol and butyl titanate solution were used in a ratio of 0.05 g: 10 mL: 25 mL, and the butyl titanate solution was prepared by mixing butyl titanate, deionized water and anhydrous ethanol in a ratio of 9 mL: 10 mL: 10 mL;
[0061] Step B3, add graphene powder to a beaker containing deionized water and ultrasonically disperse for 30 minutes, then add sodium hydroxide and ultrasonically disperse for 30 minutes, then add bromoacetic acid and ultrasonically disperse for 10 minutes, and then stir at room temperature for 10 hours. After the reaction is completed, add NHS / EDC solution and stir for 2 hours, and finally add TiO 2 -MOF was reacted at room temperature for 12 h to obtain TiO 2 -MOF / GN composites, graphene powder, deionized water, sodium hydroxide, bromoacetic acid, EDC / NHS solution and TiO 2 -MOF dosage ratio was 0.3 g:120 mL:2 g:6 g:4 mL:0.4 g, and NHS / EDC solution was prepared by stirring and mixing 4 mg EDC, 2 mg NHS, and 4 mL deionized water.
[0062] Example 4
[0063] A graphene TPV particle comprises the following raw materials in parts by weight: 4 parts of polypropylene resin (2000D), 10 parts of polyurethane resin (2000D), 4 parts of styrene resin (3000D), 4-8 parts of polyvinyl chloride resin (2000D), 1 part of silicone masterbatch, 10 parts of white oil, 20 parts of carbon black, 1 part of modified antioxidant prepared in Example 1, 4 parts of ethylene propylene rubber resin (2000D), TiO prepared in Example 1 2 -5 parts of MOF / GN composite material, 0.1 parts of tert-butyl peroxyisopropyl carbonate, 0.1 parts of trimethylolpropane triacrylate, and 5 parts of phthalocyanine green;
[0064] Step S1, weighing raw materials according to weight, mixing styrene resin and white oil for 10 minutes, and letting stand for 12 hours to obtain a first mixture;
[0065] Step S2, mixing the polypropylene resin, the polyurethane resin and the polyvinyl chloride resin, heating to 180° C., and then adding the first mixture, the silicone masterbatch, the carbon black, the modified antioxidant prepared in Example 1, the EPDM resin, the TiO prepared in Example 1 2 -MOF / GN composite material, tert-butyl peroxyisopropyl carbonate, trimethylolpropane triacrylate, and phthalocyanine green were mixed, then heated to 70°C and stirred for 10 minutes to obtain a second mixture;
[0066] Step S3, conveying the second mixture to a twin-screw extruder, heating it to 170°C, and melt-mixing it under the action of high shear force of the twin-screw extruder to obtain a polymer melt, and the polymer melt is extruded through a 10m long pipeline, cooled by spraying cooling water, air-dried, crushed and sieved to obtain graphene TPV particles. During extrusion molding, the polymer melt temperature is controlled to be 190°C, the extrusion port temperature is 170°C, and the extrusion speed is 6m / min.
[0067] Example 5
[0068] A graphene TPV particle comprises the following raw materials in parts by weight: 6 parts of polypropylene resin (2000D), 13 parts of polyurethane resin (2000D), 6 parts of styrene resin (3000D), 6 parts of polyvinyl chloride resin (2000D), 1 part of silicone masterbatch, 13 parts of white oil, 25 parts of talcum powder, 1 part of modified antioxidant prepared in Example 2, 6 parts of ethylene propylene rubber resin (2000D), TiO prepared in Example 2 2 -7 parts of MOF / GN composite material, 0.2 parts of tert-butyl peroxyisopropyl carbonate, 0.2 parts of trimethylolpropane triacrylate, and 8 parts of phthalocyanine green;
[0069] Step S1, weighing raw materials according to weight, mixing styrene resin and white oil for 15 minutes, and letting stand for 18 hours to obtain a first mixture;
[0070] Step S2, mixing polypropylene resin, polyurethane resin and polyvinyl chloride resin, heating to 200° C., and then adding the first mixture, silicone masterbatch, talcum powder, modified antioxidant prepared in Example 2, EPDM resin, TiO prepared in Example 2 2 -MOF / GN composite material, tert-butyl peroxyisopropyl carbonate, trimethylolpropane triacrylate, and phthalocyanine green were mixed, then heated to 75°C and stirred for 10 minutes to obtain a second mixture;
[0071] Step S3, conveying the second mixture to a twin-screw extruder, heating it to 175°C, and melt-mixing it under the action of high shear force of the twin-screw extruder to obtain a polymer melt, and the polymer melt is extruded through a 10m long pipeline, cooled by spraying cooling water, air-dried, crushed and sieved to obtain graphene TPV particles. During extrusion molding, the polymer melt temperature is controlled to be 190°C, the extrusion port temperature is 170°C, and the extrusion speed is 8m / min.
[0072] Example 6
[0073] A graphene TPV particle comprises the following raw materials in parts by weight: 8 parts of polypropylene resin (2000D), 15 parts of polyurethane resin (2000D), 8 parts of styrene resin (3000D), 8 parts of polyvinyl chloride resin (2000D), 2 parts of silicone masterbatch, 15 parts of white oil, 30 parts of calcium carbonate, 2 parts of modified antioxidant prepared in Example 3, 4-8 parts of ethylene propylene rubber resin (2000D), TiO prepared in Example 3 2 -5-10 parts of MOF / GN composite material, 0.3 parts of tert-butyl peroxyisopropyl carbonate, 0.3 parts of trimethylolpropane triacrylate, 10 parts of phthalocyanine green;
[0074] Step S1, weighing raw materials by weight, mixing styrene resin and white oil for 20 minutes, and letting stand for 24 hours to obtain a first mixture;
[0075] Step S2, polypropylene resin, polyurethane resin, and polyvinyl chloride resin are mixed and heated to 220° C., and then the first mixture, organic silicone additives, fillers, modified antioxidant prepared in Example 3, EPDM resin, TiO prepared in Example 3 are added. 2 -MOF / GN composite material, tert-butyl peroxyisopropyl carbonate, trimethylolpropane triacrylate, and phthalocyanine green were mixed, then heated to 75°C and stirred for 15 minutes to obtain a second mixture;
[0076] Step S3, conveying the second mixture to a twin-screw extruder, heating it to 180°C, and melt-mixing it under the action of high shear force of the twin-screw extruder to obtain a polymer melt, and the polymer melt is extruded through a 10m long pipeline, cooled by spraying cooling water, air-dried, crushed and sieved to obtain graphene TPV particles. During extrusion molding, the polymer melt temperature is controlled to be 195°C, the extrusion port temperature is 175°C, and the extrusion speed is 10m / min.
[0077] Comparative Example 1
[0078] This comparative example is a TPV particle, which is different from Example 6 in that graphene is used instead of TiO prepared in Example 3. 2 -MOF / GN composites, and the rest were the same.
[0079] Comparative Example 2
[0080] This comparative example is a TPV particle, which differs from Example 6 in that the modified antioxidant prepared in Example 3 is replaced by the antioxidant BHT, and the rest are the same.
[0081] Comparative Example 3
[0082] The comparative example is commercially available TPV plastic particles (Santoprene 111-35 from Exxon, USA).
[0083] The TPV particles of Examples 4-6 and Comparative Examples 1-3 were added to the polyurethane adhesive (purchased from Shanghai Shouxing Industrial Co., Ltd.) at a weight ratio of 1:7, and extruded together using two extruders with the same die to obtain a sample. The sheet extrusion temperature was 200°C. The VOC emission performance of the obtained sample was tested (volatile organic compounds were tested by thermal desorption / gas chromatography / mass spectrometry, the instrument model was ATD650 / Clarus680 / SQ8T, and volatile aldehydes and ketones were tested by solid phase adsorption / high performance liquid chromatography, the instrument model was LC1200), and the test standard was the enterprise standard; tensile test: a tensile machine was used to test the mechanical properties of the material (tensile strength, elongation at break). The test results are shown in Table 1:
[0084] Table 1
[0085]
[0086]
[0087] It can be seen from Table 1 that the odor of the graphene TPV particles prepared by the present invention is below 3.5 points, and the emission of benzene is 10 μg / m 3 , the emission of toluene is 100μg / m 3 The formaldehyde emission is 50μg / m 3, has good environmental performance, and it still has good tensile strength and elongation at break after hot air aging.
[0088] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A graphene TPV particle, characterized in that: The invention comprises the following raw materials in parts by weight: 4-8 parts of polypropylene resin, 10-15 parts of polyurethane resin, 4-8 parts of styrene resin, 4-8 parts of polyvinyl chloride resin, 1-2 parts of organic silicone additives, 10-15 parts of white oil, 20-30 parts of fillers, 1-2 parts of modified antioxidants, 4-8 parts of EPDM resins, 5-10 parts of TiO2-MOF / GN composite materials, 0.1-0.3 parts of vulcanizing agents, 0.1-0.3 parts of vulcanization accelerators, and 5-10 parts of pigments; The modified antioxidant is prepared by the following steps: Step A1, adding aminomethane tripropionic acid to a mixture of chloroform and acetonitrile, stirring and mixing evenly, adding trimethylsilyl chloride at room temperature, reflux for 2 hours, and then cooling to 0°C, and then adding triethylamine and trityl chloride dissolved in chloroform to the reactor, stirring the obtained mixture for 1 hour, and then adding methanol, concentrating, extracting, and drying to obtain intermediate product 1; Step A2, the intermediate product 1, triethylamine and aluminum chloride are uniformly mixed in tetrahydrofuran, and then the acryloyl chloride tetrahydrofuran solution is slowly added, and the mixture is reacted for 4-8 hours under ice-water bath and stirring conditions, and then filtered and distilled to obtain the intermediate product 2; Step A3, adding the intermediate product 2 and triethylamine to tetrahydrofuran, mixing and stirring evenly, passing nitrogen for 30 minutes to remove air, then adding 6-di-tert-butyl-4-mercaptophenol, and stirring in a 40-50° C. oil bath for 12-24 hours. After the reaction is completed, the mixture is added to 100 mL of petroleum ether for precipitation for 2 hours, and then the obtained precipitate is added to 40 mL of acetic acid solution, refluxed at 30° C. for 10 minutes, filtered and vacuum dried at 80° C. for 12 hours to obtain a modified antioxidant; The TiO2-MOF / GN composite material is prepared by the following steps: Step B1, adding 2,5-dihydroxyterephthalic acid and 2-aminopyridine to anhydrous ethanol and stirring and mixing evenly, recorded as ligand solution, then stirring and mixing copper nitrate trihydrate in deionized water, adding the ligand solution and stirring for 30 minutes, then transferring to a hydrothermal kettle and placing it at 110°C for reaction for 48 hours. After the reaction is completed, cooling to room temperature, washing with 10 mL of ethanol, filtering, soaking in 50 mL of methanol for 24 hours, washing with methanol, filtering, and vacuum drying at 120°C for 24 hours to obtain Cu-MOF; Step B2, add Cu-MOF to a beaker containing ethanol and ultrasonicate for 1 hour, then slowly add the butyl titanate solution to the beaker and ultrasonicate for 30 minutes, then stir for 1 hour, finally transfer the mixed solution to a reactor, and react at 150°C for 24 hours. After the reaction is completed, wash and freeze-dry for 24 hours to obtain TiO2-MOF; Step B3, add graphene powder to a beaker containing deionized water and ultrasonically disperse for 30 minutes, then add sodium hydroxide and ultrasonically disperse for 30 minutes, then add bromoacetic acid and ultrasonically disperse for 10 minutes, and then stir and react at room temperature for 5-10 hours. After the reaction is completed, add NHS / EDC solution and stir for 2 hours, and finally add TiO2-MOF and react at room temperature for 8-12 hours to obtain TiO2-MOF / GN composite material.
2. A graphene TPV particle according to claim 1, characterized in that: In step A1, the amount ratio of aminomethane tripropionic acid, trimethylsilyl chloride, a mixture of chloroform and acetonitrile, triethylamine, trityl chloride, chloroform and methanol is 0.01 mol: 0.01 mol: 18-20 mL: 0.02-0.03 mol: 0.01-0.025 mol: 10 mL: 2 mL, and the mixture of chloroform and acetonitrile is prepared by mixing chloroform and acetonitrile in a volume ratio of 5:
1.
3. The graphene TPV particle according to claim 1, characterized in that: In step A2, the usage ratio of the intermediate product 1, triethylamine, tetrahydrofuran, aluminum chloride, and acryloyl chloride tetrahydrofuran solution is 0.1-0.2 mol:80-100 g:100 mL:0.01-0.05 mol:100 mL, and the usage ratio of acryloyl chloride and tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 0.35-0.65 mol:100 mL.
4. The graphene TPV particle according to claim 1, characterized in that: In step A3, the usage ratio of the intermediate product 2, triethylamine, tetrahydrofuran and 6-di-tert-butyl-4-mercaptophenol is 0.01-0.02 mol: 0.2-0.4 g: 35-70 mL: 0.05-0.1 mol.
5. The graphene TPV particle according to claim 1, characterized in that: In step B1, the usage ratio of 2,5-dihydroxyterephthalic acid, 2-aminopyridine, anhydrous ethanol, copper nitrate trihydrate and deionized water is 0.03-0.04 mol: 0.01-0.02 mol: 50-100 mL: 0.06-0.08 mol: 50-100 mL.
6. The graphene TPV particle according to claim 1, characterized in that: In step B2, the dosage ratio of Cu-MOF, ethanol and butyl titanate solution is 0.01-0.05 g: 10 mL: 25 mL, and the butyl titanate solution is prepared by mixing butyl titanate, deionized water and anhydrous ethanol in the ratio of 5-9 mL: 10 mL: 6-10 mL.
7. The graphene TPV particle according to claim 1, characterized in that: In step B3, the amount ratio of graphene powder, deionized water, sodium hydroxide, bromoacetic acid, EDC / NHS solution and TiO2-MOF is 0.1-0.3 g: 80-120 mL: 1-2 g: 2-6 g: 2-4 mL: 0.2-0.4 g, and the NHS / EDC solution is prepared by stirring and mixing 4 mg EDC, 2 mg NHS and 4 mL deionized water.
8. The method for preparing graphene TPV particles according to claim 1, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, mixing styrene resin and white oil for 10-20 minutes, and letting stand for 12-24 hours to obtain a first mixture; Step S2, mixing the polypropylene resin, the polyurethane resin and the polyvinyl chloride resin, heating to 180-220° C., then mixing the first mixture, the organic silicone additive, the filler, the modified antioxidant, the EPDM resin, the TiO2-MOF / GN composite material, the vulcanizing agent, the vulcanization accelerator and the pigment, and then heating to 70-75° C. and stirring for 10-15 minutes to obtain a second mixture; Step S3, conveying the second mixture to a twin-screw extruder, heating it to 170-180°C, and melt-mixing it under the action of high shear force of the twin-screw extruder to obtain a polymer melt, and the polymer melt is extruded through a 10m long pipeline, cooled by spraying cooling water, air-dried, crushed and sieved to obtain graphene TPV particles. During extrusion molding, the polymer melt temperature is controlled to be 190-195°C, the extrusion port temperature is 170-175°C, and the extrusion speed is 6-10m / min.
Citation Information
Patent Citations
Polyester and preparation method thereof
CN101914199A
Nylon bonding and rubberizing TPV (thermoplastic vulcanizate) alloy and preparation method thereof
CN104387753A
TiO2-MOFs photocatalyst and preparation method and application thereof
CN108722497A
Heat-resistant flame-retardant unsaturated polyester resin and preparation method thereof
CN116444969A
Formaldehyde-free adhesive for straw board and preparation method of formaldehyde-free adhesive
CN117025128A